Iwan Triyuwono's Thought About The Concept Of Sharia Enterprise Theory In The Development Of Sharia Accounting Theory In Indonesia - Khairunnisa Please; Azhari Akmal Tarigan; Muhammad Yafiz (Institut Agama Islam Negeri Padngsidimpuan, 2022)
Development Theory Sharia accounting in Indonesia contributes to still emergence of debate about accountancy true and good sharia used in Indonesia. Approach formulation accountancy sharia by deductive reasoning developed by Iwan Triyuwono start the formulation with method study draft sharia established by Allah SWT in Islam. Islam regulates creed or belief, law practice, and morality. Sharia with the third meaning of the rules of the Islamic religion can conclude from the use of Sharia at the beginning spread of Islam. Consequently, action arises practice accountancy with rule sharia which is not appropriate so that in PSAK as product thinking accountancy sharia not yet implementable. Suspected problem relate with accuracy and imprecision rule sharia in arranging practice accountancy conventional this is what I tried for overcome by thinkers accountancy sharia. So that emergence theory accountancy sharia with various types thought. Development this very good for progress accountancy sharia. For example with still applied Statement Standard Sharia Accounting (PSAK) is still oriented conventional Triyuwono. Ivan Trituwono popularizes the Shariah Enterprise theory concept for repairing the very concept of Entity Theory conventional This paper will discuss thinking Ivan Triyuwono about the concept of Sharia Enterprise Theory with method Interview straight away.